Towards A Green and Sustainable Electropolishing Technology: Feasibility Studies on the Application of Choline Chloride-based Solvents for Electropolishing Aluminum - Dela Peña, Eden May; de Boda, Miguel Paolo; Napiri, Farley Sean (Philippine Engineering Journal; Vol 41 No 2 (2020), 2020)
Abstract – In this study, electropolishing of aluminum was performed using ethaline, an ionic liquid mixture of choline chloride and ethylene glycol, as polishing electrolyte. Polishing was conducted using a two-electrode system at electrode potentials of 4.5 V and 6.0 V. Electropolishing removed pre-treatment artefacts such as scratches and yielded a smooth aluminum surface. Surface analysis revealed the presence of nodular or hemispherical features in the electropolished metal. Surface roughness measurements indicate optimum electropolishing time of 25 minutes and 15 minutes at potentials of 4.3 V and 6.0 V, respectively. Ethaline is a promising ionic liquid electrolyte for electropolishing aluminum.   Keywords – electropolishing, deep eutectic solvent, aluminum, choline chloride